2017
DOI: 10.3389/fenvs.2017.00067
|View full text |Cite
|
Sign up to set email alerts
|

Subseasonal Predictability of Boreal Summer Monsoon Rainfall from Ensemble Forecasts

Abstract: Subseasonal forecast skill over the broadly defined North American (NAM), West African (WAM) and Asian (AM) summer monsoon regions is investigated using three Ensemble Prediction Systems (EPS) at sub-monthly lead times. Extended Logistic Regression (ELR) is used to produce probabilistic forecasts of weekly and week 3-4 averages of precipitation with starts in May-Aug, over the 1999-2010 period. The ELR tercile category probabilities for each model gridpoint are then averaged together with equal weight. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…Skill ranges from 0.30–0.60 in Week 1, to 0.15–0.45 in Week 2, and 0.30 or less at Weeks 3 and 4. These low skill levels in monsoon precipitation beyond the first week are consistent (and particularly at Weeks 3 and 4) with those found using extended logistic regression (Vigaud, Robertson, Tippett, & Acharya, ). While we did not exclude, a priori, the potential value of Weeks 3 and 4 forecasts, in practice, the Real‐Time Weeks 3 and 4 forecasts were never sufficiently sharp (i.e., deviating strongly from 33%) for us to have sufficient confidence in them.…”
Section: Forecast Methodologysupporting
confidence: 85%
“…Skill ranges from 0.30–0.60 in Week 1, to 0.15–0.45 in Week 2, and 0.30 or less at Weeks 3 and 4. These low skill levels in monsoon precipitation beyond the first week are consistent (and particularly at Weeks 3 and 4) with those found using extended logistic regression (Vigaud, Robertson, Tippett, & Acharya, ). While we did not exclude, a priori, the potential value of Weeks 3 and 4 forecasts, in practice, the Real‐Time Weeks 3 and 4 forecasts were never sufficiently sharp (i.e., deviating strongly from 33%) for us to have sufficient confidence in them.…”
Section: Forecast Methodologysupporting
confidence: 85%
“…There is evidence that multimodel ensembles provide increased skill over individual models on subseasonal scales (Strazzo et al, ; Vigaud, Robertson, & Tippett, ; Vigaud, Robertson, Tippett, Acharya, ), as is well established in seasonal forecasting, so that better S2S hindcast protocols that enable better calibration and bias correction can be expected to improve skill. Research is required to revisit the trade‐off between spatial resolution and ensemble size at the subseasonal range.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Efforts like the Subseasonal to Seasonal Prediction project (S2S) database (Vitart et al 2017), which freely provides a set of subseasonal forecasts and hindcasts produced by 11 different prediction systems, are helping the scientific community to advance understanding of sources of predictability, model improvement and forecast skill. Many studies have demonstrated the enhanced forecast quality of multimodel ensembles compared to a more conventional single-model ensemble approach (Hagedorn et al 2006;DelSole and Tippett 2014;Vigaud et al 2017). In addition, a large sample size allows the use of consensus between the different model forecasts to get some insight into the predictability (Piedelievre 2000), provides for an insightful evaluation of probabilistic skill (Krishnamurti et al 2006), and imparts a potential economic value to the forecast (Richardson 2000;Alessandri et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although a few studies have recently evaluated the subseasonal forecast quality and potentialities in a multisystem setting, both for precipitation (Vigaud et al 2017) and for temperature (Ferrone et al 2017), there is still no assessment regarding cold extremes at such time scale.…”
Section: Introductionmentioning
confidence: 99%